The Influence of Innovation, Network, and Technology on Customer Switching to Bank Syariah Indonesia - Hadratullah, Hadratullah; Hidayati, Rina (Indonesian Journal of Islamic Economics and Finance, 2024)
This study analyzes the influence of product innovation, service quality, and office network on switching customer behavior from conventional banks to Bank Syariah Indonesia (BSI) in Selong District. This study uses a survey method with a quantitative approach, involving 100 BSI customer respondents who were taken by purposive sampling. Data were collected through questionnaires and analyzed using simple linear regression. The study results show that product innovation significantly influences customer switching behavior, with a contribution of 40.9%, followed by information technology by 18.6%. At the same time, the office network is not significant. These findings support the Planned Behavior theory and the Diffusion of Innovation theory, which states that innovations relevant to market needs can increase the adoption of sharia services. It is recommended that BSI strengthen its digital services and unique sharia features to attract more customers, increase competitiveness, and expand market share in the Islamic banking industry in Indonesia.